3D bioprinted, vascularized neuroblastoma tumor environment in fluidic chip devices for precision medicine drug testing. (1st July 2022) - Nothdurfter, Daniel; Ploner, Christian; Coraça-Huber, Débora C; Wilflingseder, Doris; Müller, Thomas; Hermann, Martin; Hagenbuchner, Judith; Ausserlechner, Michael J
Abstract: Neuroblastoma is an extracranial solid tumor which develops in early childhood and still has a poor prognosis. One strategy to increase cure rates is the identification of patient-specific drug responses in tissue models that mimic the interaction between patient cancer cells and tumor environment. We therefore developed a perfused and micro-vascularized tumor-environment model that is directly bioprinted into custom-manufactured fluidic chips. A gelatin-methacrylate/fibrin-based matrix containing multiple cell types mimics the tumor-microenvironment that promotes spontaneous micro-vessel formation by embedded endothelial cells. We demonstrate that both, adipocyte- and iPSC-derived mesenchymal stem cells can guide this process. Bioprinted channels are coated with endothelial cells post printing to form a dense vessel—tissue barrier. The tissue model thereby mimics structure and function of human soft tissue with endothelial cell-coated larger vessels for perfusion and micro-vessel networks within the hydrogel-matrix. Patient-derived neuroblastoma spheroids are added to the matrix during the printing process and grown for more than two weeks. We demonstrate that micro-vessels are attracted by and grow into tumor spheroids and that neuroblastoma cells invade the tumor-environment as soon as the spheroids disrupt. In summary, we describe the first bioprinted, micro-vascularized neuroblastoma—tumor-environment model directly printed into fluidic chips and a novel medium-throughput biofabrication platform suitable for studying tumor angiogenesis and metastasis in precision medicine approaches in future.